2017
DOI: 10.1128/jvi.00958-17
|View full text |Cite
|
Sign up to set email alerts
|

Differentiated Human SH-SY5Y Cells Provide a Reductionist Model of Herpes Simplex Virus 1 Neurotropism

Abstract: Neuron-virus interactions that occur during herpes simplex virus (HSV) infection are not fully understood. Neurons are the site of lifelong latency and are a crucial target for long-term suppressive therapy or viral clearance. A reproducible neuronal model of human origin would facilitate studies of HSV and other neurotropic viruses. Current neuronal models in the herpesvirus field vary widely and have caveats, including incomplete differentiation, nonhuman origins, or the use of dividing cells that have neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 161 publications
(109 reference statements)
2
42
0
Order By: Relevance
“…These differentiated cells are characterized by the formation of extensive neurites, as well as the induction of neuron-specific enzymes, receptors, and neurotransmitters ( 42 ). Differentiated SH-SY5Y cells have been used as models for neuron-virus interactions ( 66 ) including EV-A71 ( 54 , 55 ), chikungunya virus ( 60 ), and varicella-zoster virus ( 59 ). Our results show that both differentiated and undifferentiated SH-SY5Y can be infected with neurotropic strains of EV-D68, suggesting neurotropic strains of EV-D68 can invade both immature and mature neuronal cells.…”
Section: Discussionmentioning
confidence: 99%
“…These differentiated cells are characterized by the formation of extensive neurites, as well as the induction of neuron-specific enzymes, receptors, and neurotransmitters ( 42 ). Differentiated SH-SY5Y cells have been used as models for neuron-virus interactions ( 66 ) including EV-A71 ( 54 , 55 ), chikungunya virus ( 60 ), and varicella-zoster virus ( 59 ). Our results show that both differentiated and undifferentiated SH-SY5Y can be infected with neurotropic strains of EV-D68, suggesting neurotropic strains of EV-D68 can invade both immature and mature neuronal cells.…”
Section: Discussionmentioning
confidence: 99%
“…The human neuroblastoma cell lines SH-SY5Y and BE(2)-M17 are two of the best-characterised cell lines for studies into human neurological disease, such as Alzheimer’s and Parkinson’s diseases (3035), and neurovirology (3946, 49, 52). Previous studies have confirmed their suitability as in vitro models of human neurons due to their expression of human neuron-specific markers, and the fact that their neuron-like phenotypes can be further improved through the use of chemical differentiation agents, such as RA and staurosporine (3638, 43).…”
Section: Discussionmentioning
confidence: 99%
“…Both differentiated and undifferentiated SH-SY5Y and BE(2)-M17 cells have been previously used for in vitro studies with a range of neurotropic viruses, including herpes viruses (3941), neurotropic enteroviruses (42, 43), chikungunya virus (44), poliovirus (45), various orthobunyaviruses (46), henipaviruses (47, 48), and Zika virus (49). In a number of these studies, growth in SH-SY5Y and BE(2)-M17 cells differed based upon whether the strains involved were virulent or attenuated in vivo , with neurovirulent viruses reaching higher titres than attenuated ones (43, 45).…”
Section: Introductionmentioning
confidence: 99%
“…Cellular uptake of Cf-HSV peptides into host cell model [4][5][6], SH-SY5Y human neuroblastoma cells [7][8][9] was characterised by the enhanced intracellular fluorescence measured by BD LSR II flow cytometer (Coherent Sapphire laser; λ = 488 nm, 22 mW) (incubation time: 3h; channel FITC LP505; BP 530/30), data were analysed with FACSDiva 5.0 software. All measurements were performed in duplicates, and the Cf-positive (Cf+) live cells with standard error of the mean was presented ( Figure 1).…”
Section: Methodsmentioning
confidence: 99%